Unpredicted respiratory arrest following hypoglossal nerve palsy during subarachnoid hemorrhage: Experimental study (Annals of Medical Research, 2021)
Aim: Although acute respiratory arrest is the most dangerous complication of subarachnoid hemorrhage; if there is any association between hypoglossal nerve-tongue palsy induced acute mechanical upper airway obstruction has not been extensively described so far. Our aim is to evaluate if there is a relationship between hypoglossal ischemia-tongue paralysis and upper airway obstruction during subarachnoid hemorrhage. Materials and Methods: Formerly studied 23 rabbits’s documents chosen from our SAH experiments. A control group (Group A) include 5 normal animals, Sham group (Group B) include 5 animals which saline was administered, and a study group (Group C) include 13 animals (7 survive-C1 / 6 dead-C2) which were injected with homologous blood into the cisterna magna. Blood pressure values and and electrocardiograhic changes were recorded per days of all animals before, during and after surgery during two weeks and all animals decapitated under general anesthesia. Hypoglossal nerves, tongue muscles and upper arways were evaluated. Numbers of degenerated axons/neurons density of hypoglossal nerves-atrophic tongue muscles and airway obstruction scores (AOS) of all animals were determined and analysed statistically with ANOVA. AOS was classified according to tongual sliding down distances to larynx numbered between 1-7 mm to scored with 1-7.Results: Important neurodegeneration was noticed in axons of the hypoglosssal nerves and tongue muscle denervation injury was in more severe in AOS observed animals. The hypoglossal nerves, degenerated axon density (n/mm2), numbers of atrophic muscles (n/mm3) and AOS was: 4±2, 1±1, 1±1 in A; 7±3, 2±1, 2±1 in B and 98±11, 23±5, 5±2 in C1 groups. P values between the axonal degeneration of hypoglossal nerves/muscles and AOS was p0.005 for C2/C1; p0.0005 for C2/A and p0.0001 C2/B.Conclusion: Hypoglossal ischemia induced tongual muscle palsy related respiratory arrest should be remembered in neurocritical cases. Maintaining normal respiratory functions is only possible with airway tone, which is possible with an intact hypoglossal nerve.
Keywords: Hypoglossal palsy; respiratory disfunctions; subarachnoid hemorrhage